THE MECHANISM FOR GRANTING THE STATUS OF A CHILD WHO HAS BEEN INJURED AS A RESULT OF MILITARY ACTIONS AND ARMED CONFLICTS - Beluga, Yuliia (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2022)
One of the most important tasks of a modern democratic society is the protection of the rights of children. It is explained by the fact that juveniles, due to their mental and physical unformedness, are a particularly vulnerable category of the population, which becomes more complicated in crises, especially during military operations and armed conflicts. The mechanism for granting the status of a child affected (injured) by hostilities and armed conflicts must be considered in the system of a legal mechanism for ensuring his right to social protection. A simplified procedure for obtaining the status of a child affected by military actions and armed conflicts is not enough; a comprehensive approach is required to ensure the social protection of such children. After all, today no guarantees are provided for minors, who grow up in war conditions, except for free hot meals in state and communal educational institutions. Accordingly, a system of logistical, organizational, managerial, and special legal measures and means should be created aimed at effective legal regulation of the social protection of children affected by hostilities and armed conflicts, to realize the right to social protection by actually obtaining specific types of it (cash payments, social services, in-kind assistance, social benefits, medical assistance, medicines, and medical products). Purpose: to reveal the mechanism for granting the status of a child affected (injured) by military actions and armed conflicts, as part of the legal mechanism for ensuring his right to social protection. Methods: formal-logical method and system analysis method, structural-functional method, and other well-known research methods. Results: the procedure and conditions for granting the status of a child affected by hostilities and armed conflicts were analyzed. Discussion: the legal discussion in the scientific paper is led concerning the advisability of applying an integrated approach to ensure the social protection of children affected by military actions and armed conflicts.